Vaccines, Immunotherapy and New Antifungal Therapy Against Fungi: Updates in the New Frontier - Carlos P. Taborda (Frontiers Research Topics, 2017)
Invasive fungal diseases have increased many fold over the past 50 years. Current treatment regimens typically require prolonged administration of antifungal medications that can have significant toxicity. Moreover, our present potent antifungal armamentarium fails to eradicate fungal pathogens from certain compromised hosts. Additionally, invasive fungal diseases continue to have unacceptably high mortality rates. A growing body of work has focused on the utility of vaccines and/or immunotherapy as a powerful tool in combating mycoses, either for the active treatment, as an adjuvant, or in the prevention of specific fungal pathogens. Also, it is growing the interest over new drugs development as second choice for treatment when traditional chemotherapy fail. This Research Topic will detail the exciting progress in developing vaccines, immunotherapy and new drugs for fungi.